X‐ray structure of a human cardiac muscle troponin C/troponin I chimera in two crystal forms. Issue 1 (16th December 2021) - Yan, Chunhong; Sack, John S.
Abstract : The X‐ray crystal structure of a human cardiac muscle troponin C/troponin I chimera has been determined in two different crystal forms and shows a conformation of the complex that differs from that previously observed by NMR. In contrast to previous models, the troponin I helix runs in a parallel direction relative to the troponin C groove and completely blocks the calcium desensitizer binding site of the troponin C–troponin I interface. Abstract : The X‐ray crystal structure of a human cardiac muscle troponin C/troponin I chimera has been determined in two different crystal forms and shows a conformation of the complex that differs from that previously observed by NMR. The chimera consists of the N‐terminal domain of troponin C (cTnC; residues 1–80) fused to the switch region of troponin I (cTnI; residues 138–162). In both crystal forms, the cTnI residues form a six‐turn α‐helix that lays across the hydrophobic groove of an adjacent cTnC molecule in the crystal structure. In contrast to previous models, the cTnI helix runs in a parallel direction relative to the cTnC groove and completely blocks the calcium desensitizer binding site of the cTnC–cTnI interface.